Treatment of sialorrhea with botulinum toxin injections in pediatric patients less than three years of age. (July 2022) - Fan, Timothy; Frederick, Robert; Abualsoud, Ahmad; Sheyn, Anthony; McLevy-Bazzanella, Jennifer; Thompson, Jerome; Akkus, Cem; Wood, Joshua
Abstract: Objective: To determine the patient demographics and the efficacy and safety profile of botulinum toxin (BTX) injections for sialorrhea control in patients under the age of three. Methods: This is a retrospective chart review study. Patients under three years of age who received BTX injections for sialorrhea management from 2010 to 2021 were assessed. Patient demographics, comorbidities, medical and surgical histories, indications, BTX injection details, and post injection complications were documented. Results: Forty-nine patients met inclusion criteria. The most common patient under three years of age with sialorrhea to receive BTX injections were white (51.0%) male (51.0%) with congenital (73.5%) and/or neurologic (53.1%) comorbidities. Thirty-six (73.5%) patients were from medically underserved areas/populations. Our patients on average received 1.7 injections, with 44.9% requiring multiple BTX injections. Bilateral parotid and bilateral submandibular glands (four-gland) BTX injections were associated with significant decrease in admissions for pneumonia and cessation of anticholinergics usage (both P < 0.05). Post BTX injections, 15 (30.6%) patients required additional surgeries for sialorrhea control. No adverse outcomes due to BTX injections were reported. Conclusions: Pediatric sialorrhea was commonly associated with congenital and/or neurologic comorbidities and disproportionately impacted medically underserved black patients. BTX injections offered multifaceted benefits for controlling sialorrhea in patients under the age of three. Four-gland BTX injections led to reduction of unnecessary hospitalization, usage of anticholinergics, and additional surgeries for sialorrhea management. Highlights: Patients with sialorrhea often have multifactorial risk factors, warranting comprehensive assessment and treatment plans. Botulinum toxin injections may be beneficial for reducing sialorrhea induced pneumonia and its related hospitalizations. Botulinum toxin injections are beneficial for weaning patients off anticholinergics and for reducing associated side effects. Nearly 2/3 of patients post botulinum toxin injections do not require additional surgeries for sialorrhea control. Botulinum toxin injections are safe and effective for sialorrhea management for patients less than three years of age.